Analytics for awareness in maritime surveillance: from data to tactical insight. (April 2019) - Caelli, Terry; Mukerjee, Joyanto; Sparks, Evan
Although significant effort has occurred into developing realistic simulation environments for maritime surveillance, relatively little attention has been given to objectively summarizing and providing platforms for querying the mission simulation outputs for post-mission debriefing purposes. In this paper we adopt recently proposed data analytic ideas for this context and illustrate the proposed approach using multi-layered statistical methods from visualization to Bayesian network-based data interpretation models. Analyzing example missions in these terms demonstrates the potential use for such technologies for objective and insightful post-mission analyses.